Diksi dan Citraan dalam Naskah Drama Kamit Karya Gusmel Riyadh (Kajian Stilistika) - Sari, Ayu Kumala, Prof.Dr.Ali Imron Al-Ma'ruf,M.Hum (2017)
This research aims to (1) describe the structur of Kamit drama script by Gusmel Riyadh, (2) describe the dictions of Kamit drama script by Gusmel Riyadh and that is studied by stylistic, (3) Describe the sense of Kamit done script by Gusmel Riyadh that is studied by stylistic, (4) describe the meaning taired in Kamit done script, (5) describes the implementasy of the research results diction and sense ofKamit done script by Gusmel Riyadh that is literature teaching in vocational school. This is qualitative research. The techniques of collecty data are diving manual and recording. The data validity uses triangulation theory. The technique of analysis datais stylistic. (1) The diction of Kamit drama script by Gusmel Riyadh are conotative, concrete, adaption from foreign language, typical greeting or personal names, Java exclamation, vulgar words, words with object of reality nature, and Java vocabulary. (2) The sense of Kamit drama by Gusmel Riyadh are sight, hearing, smell, move, task, and intellectual. (3) The meaning contained in Kamit drama script by Gusmel Riyadh are social dimention: the empaty towards wong cilik (poor), moral dimention: the moral defected by culture, and religion dimention. (4) There are three criteria the selection of literature teaching materials, languge, psychology, and cultural backgrounds, where three very important to get the appropriate literature teaching materials.